Clinical analysis of spinal hemangioblastoma: report of 7 cases with litertures review - Huan⁃yu WANG; Hong WANG; Quan⁃feng MA; Yuan TIAN (Chinese Journal of Contemporary Neurology and Neurosurgery, 2020)
Objective To summarize the treatment experiences and surgical measure and efficacy of spinal hemangioblastoma. Methods and Results The surgical experiences of 7 patients with spinal hemangioblastoma from February 2012 to February 2017 in Tianjin Huanhu Hospital were analyzed retrospectively. Spinal MRI showed occupying lesion, empty vessel signals and syringomyelia (SM), with enhancement, All patients underwent microsurgical resection, and total resection was achieved (total excision in 5 cases and focus of responsibility total resection in 2 cases). Pathological examination confirmed hemangioblastoma. After operation, 6 cases improved, one case had no change, and no one died. During follow⁃up period, 5 cases was McCormick Scale Ⅰ, one was McCormick Scale Ⅱ, and one was McCormick Scale Ⅲ. No tumor recurrence was found. Conclusions The spinal hemangioblastoma is highly vascularized benign intramedullary tumors that can be cured surgically under microscopy.